ANALYSIS OF THE EFFECT OF SERVICE QUALITY ON TREATMENT DECISIONS AND PATIENT LOYALTY IN THE OUTPATIENT UNIT OF MAMPANG PRAPATAN HOSPITAL JAKARTA - Cucu Nurgahawan; Nurminingsih; Dinni Agustin (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
Hospital service quality is the main thing in an effort to improve treatment decisions that will bring patient loyalty. This study aims to analyze the effect of service quality on treatment decisions and patient loyalty in the outpatient unit of Mampang Prapatan Hospital, Jakarta. This study is a quantitative study using SEM analysis to see the relationship between service quality and treatment decisions and patient loyalty. Using a total of 148 respondents with a questionnaire instrument with good validity and reliability values. The direct influence of service quality on patient loyalty resulted in t value = 7,99 Test the indirect effect of service quality on loyalty through treatment decisions t value = 4,83. The results of the test of the direct influence of service quality t = 5,64, the test of the indirect influence of quality on treatment decisions through loyalty t = 5,18. Therefore, it can be concluded that there is a significant effect of service quality on loyalty directly and indirectly through treatment decisions. Besides that, there is a significant effect of service quality on treatment decisions directly and indirectly through patient loyalty.